Pulmonary Arteriovenous Malformation Causing Systemic Hypoxemia in Early Infancy - Aggarwal, V. (Case Rep Pediatr, 2017)
Pulmonary arteriovenous malformation (AVM) is not routinely appreciated during the standard echocardiogram to assess for structural abnormalities or pulmonary hypertension. The distal pulmonary AVM is suspected only if an injection of agitated saline is performed and late entry of particles is appreciated in the left heart structures. A large or complex pulmonary AVM can result in significant right-to-left shunting and consequential systemic hypoxemia in the presence or absence of pulmonary hypertension. For direct visualization of the pulmonary AVM, computerized tomography (CT) scan is the procedure of choice. Here, we present two young infants with systemic hypoxemia who underwent standard medical management including mechanical ventilation and one patient was placed on extracorporeal membrane oxygenation (ECMO) before the diagnosis of pulmonary AVM was established. Subsequently, both patients have done well into mid-term follow-up after being treated successfully using transcatheter occlusion techniques in the cardiac catheterization laboratory during early infancy. We aim to emphasize the importance of a high index of suspicion for pulmonary AVM in infants with refractory systemic hypoxemia of unclear etiology.